Family Planning Village: From Gapura to Family Quality of Life - Hasan, Mohammad Tohirin; Iswandi, Iswandi (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2020)
Since its launch in 2016, the Family Planning Village (Kampung KB) has experienced interesting dynamics in the field. The number of KB Kampung is increasing every year. One of the goals of the KB Village is to improve the family quality of life. Quality of life consist of the physical, emotional, social, intellectual, spiritual, and environmental dimensions. This literature review research explores two questions: (1) how is the implementation of KB Kampung in the field; (2) What are the implications of Kampung KB for the quality of family life. By using Crossref and Google Scholar, 97 writings on the theme of Kampung KB were obtained. After the exclusion, there were 33 papers that were relevant to the purpose of this study, only 23 papers were obtained which were used as exploration material. The results of the analysis show several things. First, Kampung KB has been implemented with various obstacles and opportunities. Some that are often encountered are: lack of understanding of the managers, lack of budget support, and low continuity of activities. Second, although the community has felt the benefits, the programs and activities have not had too many implications for the family quality of life.